Plasma Biochemistry Profiles Of Wild Western Tiger Snakes (Notechis Scutatus Occidentalis) Before and After Six Months of Captivity - Lettoof, Damian C.; Aubret, Fabien; Spilsbury, Francis; Bateman, Bill; Haberfield, J.; Vos, J.; Gagnon, Marthe Monique (2021)
Urban wildlife often suffer poorer health than their counterparts living in more pristine environments due to exposure to anthropogenic stressors such as habitat degradation and environmental contamination. As a result, the health of urban versus nonurban snakes might be assessed by differences in their plasma biochemistries. We compared the plasma profiles of western tiger snakes (Notechis scutatus occidentalis) from a heavily urbanized wetland and a natural, nonurbanized wetland. Despite the urbanized snakes having lower body mass index, we found no significant difference between the plasma profiles of the two populations. We collected snakes from each population and kept them in captivity for 6 mo, providing them with stable conditions, uncontaminated (exempt from heavy metals and pesticides) food and water, and lowered parasite intensity in an attempt to promote better health through depuration. After captivity, snakes experienced a significant improvement in body mass index and significant changes in their plasma profiles. Snakes from the natural wetland initially had more variation of DNA damage; mean concentration of DNA damage in all snakes slightly decreased, but not significantly, after captivity. We present the plasma biochemistry profiles from western tiger snakes both before and after captivity and suggest a period of removal from natural stressors via captivity may offer a more reliable result of how plasma profiles of healthy animals might appear.